Market power, productivity and the EU single market program: An ex-post assessment on Italian firm level data - Anna Bottasso; Alessandro Sembenelli (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper provides empirical evidence on the impact the EU Single Market Program has exerted on market power and total factor productivity in a large sample of Italian firms. By splitting the full sample on the basis of the ex-ante likelihood of being affected by the removal of non-tariff barriers within EU boundaries, we are able to control for other economic shocks, provided they affect all firms randomly. Both market power and total factor productivity are estimated by applying several extensions of the methodology developed by Hall. Main findings can be summarised as follows. Firstly, for the sample of "most sensitive" firms market power decreases by 50% in the SMP implementation period compared to previous years, whereas no clear pattern emerges for the other sub-samples of firms. Secondly, only for the sub-sample of "most sensitive" firms a positive transitory shock to productivity growth rates is observed immediately after the announcement of the reform project. Overall, these results are consistent with the long standing view that economic integration reduces firms' market power and increases productivity via the removal of non-tariff barriers.
Keywords: L1; O3; F1; 330; Market power; Productivity; Integration; Europe; Marktmacht; Produktivität; EU-Binnenmarkt; Unternehmenserfolg; Italien